Activity of Ethanol Extract of Kalangkala seed (Litseaangulata B.) as Nephroprotector and Hepatoprotector in Alloxan-induced Diabetic Rats - Daipadli, Daipadli; Mahfudh, Nurkhasanah; Yuliani, Sapto (South Eastern European Journal of Public Health, 2024)
Kalangkala (Litsea angulata B) is a traditional medicine that contains phenolic compounds and flavonoids and has antioxidant activity. Phenolic and flavonoids are reported to protect liver and kidney function and maintain insulin levels in the body. The purpose of this study was to determine the effect of administration of ethanol extract of kalangkala seeds (EEBK) as nephroprotective and hepatoprotective agents in rats (Rattus norvegicus L) induced by alloxan. Kalangkala seed was extracted by ethanol and evaporated to get the concentrated extract. The 30 male Wistar rats were divided into 6 groups including normal group, negative group, metformin positive group and treated groups which treated by EEBK 100, 200 and 400 mg/kgBW. Alloxan was injected intraperitoneally, metformin and EEBK were given orally for 21 days. The blood of rats was taken through the orbital sinus on day 21. The results showed the total flavonoid content of EEBK was 6.27 mgQE/g. EEBK doses of 100, 200 and 400 mg/kg BW as well as metformin can reduce (p<0.05) creatinine levels, ureum and SGPT activity but only EEBK doses of 200 and 400 mg/kgBW (p<0.05) can reduce SGOT activity. The administration of EEBK doses of 100. 200 and 400 mg / kgBW was able to improve the histopathological picture of the liver. It can be concluded that EEBK has the potential as a nephroprotective and hepatoprotective in diabetic rats (Rattusnorvegicus L) induced by alloxan